2016
DOI: 10.4049/jimmunol.1501041
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for P2X7 Receptor–Induced VCAM-1 Shedding and Neutrophil Infiltration during Acute Lung Injury

Abstract: Pulmonary neutrophils are the initial inflammatory cells that are recruited during lung injury and are crucial for innate immunity. However, pathological recruitment of neutrophils results in lung injury. The objective of this study is to determine whether the novel neutrophil chemoattractant, soluble VCAM-1 (sVCAM-1), recruits pathological levels of neutrophils to injury sites and amplifies lung inflammation during acute lung injury. The mice with P2X7 receptor deficiency, or treated with a P2X7 receptor inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 64 publications
(63 reference statements)
3
41
0
1
Order By: Relevance
“…VCAM‐1 also mediates the chemotactic activities of neutrophils and activates alveolar macrophages . In the present study, a high concentration of VCAM‐1 was detected in BALF following LPS induction of ALI, and this result is consistent with the observation that blocking of alveolar VCAM‐1 activity is protective in ALI . The p38 MAPK pathway has also been shown to play a critical role in regulating VCAM‐1 expression .…”
Section: Discussionsupporting
confidence: 91%
“…VCAM‐1 also mediates the chemotactic activities of neutrophils and activates alveolar macrophages . In the present study, a high concentration of VCAM‐1 was detected in BALF following LPS induction of ALI, and this result is consistent with the observation that blocking of alveolar VCAM‐1 activity is protective in ALI . The p38 MAPK pathway has also been shown to play a critical role in regulating VCAM‐1 expression .…”
Section: Discussionsupporting
confidence: 91%
“…38 An antagonist of the P2X7 receptor, AZ106006120, reduces neutrophil infiltration and the secretion of pro-inflammatory cytokines in a mouse model of acute lung injury. 151 Several P2X7 antagonists are in clinical trials for inflammatory or pain-related diseases. Unfortunately, AstraZeneca's AZD-9056 and Pfizer's CE-224,535 failed in phase II clinical trials.…”
Section: P2x7 Antagonistsmentioning
confidence: 99%
“…PMNs are the most abundant circulating leukocytes in humans and play important roles in the innate immune response through rapid recruitment into sites of infection and injury . However, overproduction of hydrolytic enzymes and ROS by PMN have been considered major causes of PMN‐mediated damage to local surrounding tissues . PMN apoptosis, a form of regulated noninflammatory cell death, has been reported as an effective approach to control the number of local PMNs, thereby facilitating a negative‐feedback mechanism for inflammation and promoting its resolution .…”
Section: Introductionmentioning
confidence: 99%
“…5 However, overproduction of hydrolytic enzymes and ROS by PMN have been considered major causes of PMN-mediated damage to local surrounding tissues. 6 PMN apoptosis, a form of regulated noninflammatory cell death, has been reported as an effective approach to control the number of local PMNs, thereby facilitating a negative-feedback mechanism for inflammation and promoting its resolution. 7 However, emerging evidence has shown that other types of regulated inflammatory PMN death may also occur during inflammation, which can exaggerate inflammation through release of DAMPs.…”
Section: Introductionmentioning
confidence: 99%